Moving between ethics and emptiness - Sastré Pérez, Daniela Alejandra (Emerging Trends in Education, 2024)
Reviewed book: Lo Posthumano. Braidotti, R. (2015). Editorial Gedisa.With Lo Posthumano, Rosi Braidotti continues analyzing the position of ethics and philosophy for the construction of a transdiscipline that does not get bogged down in academic duties and that retakes the human sense for the benefit of society.